EFFECT OF FLUSHING ON REPRODUCTIVE PERFORMANCE AND SYNCHRONIZATION OF ESTRUS IN TELLICHERRY DOES - MUTHURAMALINGAM, T; POTHIAPPAN, P; GNANARAJ, P TENSINGH; DEVI, T; RANGASAMY, S (The Indian Journal of Animal Reproduction, 2023)
The study was undertaken in Tellicherry goats under uniform management and feeding regimen. A total number of 30 does were selected twenty days after kidding and utilized for the study in an organized goat farm at Chennai. All the selected goats were fed with 350 grams of concentrate which was 100 grams more than a normal ration. All does were supplemented with Injection.Sodium acid Phosphate, Vitamin AD3EK and multi vitamin syrup containing folic acid and riboflavin. lntravaginal progesterone impregnated sponges were inserted on zero day. On 10th day, Cloprostenol 125 μg I/M was given and on day eleven, the sponges were removed and lnj. PMSG 200 IU I/M was administered. On day thirteen, the goats were allowed for fixed natural mating at 8 hours interval. All does were allowed for pen mating. Early pregnancy diagnosis was carried out by ultrasonography from the day after 30 days of mating. In the present study, the conception rate obtained in the present study was 93 per cent (28/30). It can be concluded that flushing before breeding and progesterone containing intra vaginal sponge, PMSG and PGF 20 combinations can be used for effective synchronization of estrus and improved conception rate in goats.